PENGARUH PENGGUNAAN VIDEO POWTOON TERHADAP PEMAHAMAN MATERI NORMA DAN ATURAN SISWA SEKOLAH DASAR - Ninis Choirun Nisa’; Irianto, Apri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The lack of innovative learning media makes it difficult for students to receive material delivery from teachers. One of them is norms and rules material for elementary school students. Teacher should be more innovative in choosing media for the teaching process. Powtoon videos are a suitable medium for conveying norms and rules material because with very interesting features it can increase students understanding of norms and rules material. This research methodology includes data collection and analysis steps. This research was carried out using the Quasi Experimental Design method. The instrument used was the result of the posstest test which proved that the video media had a significant effect on the understanding of the norms and rules of elementary school students. Based on the result of the hypothesis test using the spss application version 21 shows that it is known that sig. (2-tailed) has values of 0.040 and 0.041, it can be concluded that “Ha” is accepted and “Ho” is rejected. This proves that video media is influential in understanding the norms and rules of elementary school students.